Phytochemical analysis and screening of antibacterial activity of some selected Indian medicinal plants - C. Arora Chugh,; D. Bharti, (International Journal of Phytomedicine, 2012)
Phytochemical screening and evaluation of antibacterial activity of ten plant species namely Aloe barbadensis, Aegel marmelos, Azadirachta indica, Bahunia variegate, Cannabis sativa, Emblica officinalis, Eugenia jambolana, Gmelina arborea, Nerium oleander and Vitex negundo have been carried out against six bacterial strains namely Escherichia coli 101, Escherichia coli 119, Micrococcus luteus, Bacillus subtilus, Bacillus cereus and Pseudomonas fluorescence. All the plants species taken in present study have shown the presence of tannin, flavonoids, terpenoids and alkaloids. Pholobatanins have found to be present in Aegel marmelos, Bahunia variegate and Eugenia jambolana while cardiac glycosides have been shown positive test on Aloe barbadensis, Azadirachta indica, Cannabis sativa, Nerium oleander and Vitex negundo. Methanol extract of Emblica officinalis have been shown significance potential against all test pathogens except Pseudomonas fluorescence followed by Nerium oleander, Azadirachta indica and Bahunia variegate.